Effect of Dayak Onion (Eleutherine palmifolia (L) Merr. Crude Extract on Histopatology of Gills, Kidney, Liver and Muscle of Aeromonas hydrophila- Infected Carp (Cyprinus carpio) - Maftuch Maftuch; H. Suprastyani; E. Sanoesi; N. Farida; I. Fransira; N. Habibah; Dwi R. Fatmawati; R. Rinaldi; Ika K. Nisyak; D. Ardiansyah; Asep A. Prihanto (Program Pascasarjana Universitas Brawijaya, 2018)
Carp (Cyprinus carpio) is one of important freshwater cultivated fish species in Indonesia. Aeromonas hydrophila is accounted as potential pathogenic bacteria in Carp, Hence the control for the infection of A. hydrophila is very important. In this study we investigated the effectiveness of crude extract of Dayak onions (Eleutherine palmifolia (L.) Merr) for the treatment of A. hydrophila infected fish. Furthermore, alteration of histophatology of several organs, gills, kidney, liver and muscle were also investigated. Crude Extract of Dayak Onion (Eleutherine palmifolia (L) Merr. (CEDO) with the doses of 50, 60, 70 and 80 ppm were used for treatment of A. hydrophila infected carp for 11 days. Prior to investigation of histopatology of gills, kidneys, hearts, muscle, the Carp was moved to fresh-non infected fish tank. The Result indicated that gill experienced Hyperplasia, Fusion, Necrosis. Kidney experienced Degeneration, Congestion, Necrosis. Liver experienced the vacuole degeneration, congestion, Melano macrophages, necrosis. Muscle experienced Edema and necrosis. But fish treated with 80 ppm treatment showed less damage and tissue repair.Keywords : E. palmfolia (L.) Merr, A. hydrophila, C. carpio, Histopathology, Gills, Kidney, Liver, Muscle